Is normalized hindlimb length measurement in assessment of thyroid disruption in the amphibian metamorphosis assay relevant?. Issue 8 (8th April 2019) - Pawlowski, Sascha; Dammann, Martina; Weltje, Lennart; Champ, Samantha; Mathis, Michael; Fort, Douglas J.
Abstract: The amphibian metamorphosis assay represents an OECD Level 3 and EDSP Tier 1 ecotoxicity test assessing thyroid activity of chemicals in African clawed frog ( Xenopus laevis ). To evaluate the effectiveness of snout‐vent length (SVL) normalization of hindlimb length (HLL), correlation between the HLL and SVL or body weight was evaluated in the control groups of 10 individual studies from three laboratories. Two studies required separate analysis of the Nieuwkoop‐Faber (NF) stage ≤60 and >60 animals creating a total of 12 data sets. On study day 7, significant positive correlation between HLL and SVL or body weight was observed in eight and seven of the 10 data sets, respectively ( r  = 0.608‐0.843 and 0.583‐0.876). On study day 21, significant positive correlation between HLL and SVL or body weight was found in three and four of the 12 data sets, respectively ( r  = 0.452, 0.480 and 0.553 and r  = 0.621, 0.546, 0.564 and 0.378). Significant positive correlation between HLL and SVL was found in three of five studies, including ≤NF stage 60 data ( r  = 0.564, 0.546 and 0.621). In one of eight studies, including >NF stage 60 data, the positive correlation between HLL and body weight was determined ( r  = 0.378). Negative or no correlation between HLL and SVL or body weight was found in the other late stage data sets. Therefore, use of SVL‐normalized HLL to assess thyroid‐mediated effects in X. laevis tadpoles is not warranted. HL stage relative to body stage should be considered. Abstract : To evaluate normalized hindlimb length (HLL), the correlation between HL and either snout‐vent length or body weight was evaluated in the controls from 10 independently performed amphibian metamorphosis assay studies at study days 7 and 21. Based on the analysis, the HLL should not be used to assess thyroid axis activity, but a comparison of the developmental stage of the HL with the developmental stage of the rest of the larval body could be used more effectively to assess asynchronous development indicative of hypothalamic‐pituitary‐thyroid axis activity.